PENGARUH PENYEMPURNAAN PETA KONSEP YANG DIIKUTI METODE PERMAINAN SPOTLIGHT TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMPN 2 BAYANG KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Putri, Dini Eka; Ardi, Ardi; Nursyahra, Nursyahra (STKIP PGRI Sumbar, 2013)
ABSTRACTThe purposes of this research was to know the effect of completing concept map that followed by spotlight games on biological study achievement at class 2 of SMPN 2 Kecamatan Bayang, Kabupaten Pesisir Selatan. This research was an experimental research which is used randomize design. The population was all of the studentâs at class VII of SMPN 2 Bayang which are registered for academic year in 2012/2013 at second semester. They are divided into 7 classes. The sample is gotten from randomize way. The sample was class VII6 as experimental class and VII5 as the control class. The data analysis is used the t-table at 0,05 as the passing grade. Based on the hypothesis testing, the value of t-calculation (4,68) was bigger than t-table (1,64). Itâs mean that hypothesis is accepted. Therefore it can be concluded that completing concept map that followed by spotlight games can increase studentâs biology achievement at at class 2 of SMPN 2 Kecamatan Bayang in academic year 2012/2013.Â Â